PENGARUH MODEL PEMBELAJARAN DAN TINGKAT KEMAMPUAN AKADEMIK TERHADAP PEMAHAMAN KONSEP MATEMATIS - Bolisma Welinda; Mulia Suryani; Anna Cesaria; Ramadoni Ramadoni (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research is motivated by the understanding of students' mathematical concepts in the learning process which is still low. The purpose of this study was to determine whether there is an effect of learning models on students' understanding of mathematical concepts and to determine whether there is an effect of students' academic ability level on students' understanding of mathematical concepts in Phase F IPA MAN 1 Padang Pariaman. This type of research is posstest-only control group design. This study uses the one-sample kolmogorof-smirnov method to determine whether the data under study is normally distributed. The data analysis technique in this study is the ANCOVA Test with the help of SPSS 22.0 Windows. From the results of the ANCOVA Test calculation, the sig value = 0.000 is obtained which means sig <0.05 then H_0 is rejected, so it can be concluded that there is a significant effect of the learning model on the understanding of mathematical concepts of Phase F science students MAN 1 Padang Pariaman. For the level of students' academic ability, sig < 0.05 is obtained, so it can be concluded that the level of students' academic ability affects the understanding of students' mathematical concepts.